Analysis of Key Financial Indicators of Telecommunications Companies in European Union and Baltic Sea Region - Mackevičius, Jonas; Radavičius, Stanislovas (Ekonomika, 2002)
We are currently experiencing enormous growth in the methods, speed, coverage, and global reach connectivity. Voice and data transfer are reaching a threshold that takes them beyond into a new level of quality. However, European telecommunications market is experiencing a crisis today. There are several reasons for that - companies over - invested in infrastructure largely supported through debt and vendor financing before demand actually materialized and telecommunications licenses that were purchased by European carriers also had a huge impact on carrier’s financial strength.In order to make a proper analysis of financial strength of telecommunications carriers in the European Union and Baltic countries it was important to get the necessary data that could be compared. However, financial statement forms as well as financial terms in the statements prepared by the companies were different, and that complicated the analysis.The analysis of the largest telecommunications carriers in the European Union (“Deutsche Telkom”, “Telia”, “France Telecom” and “British Telecommunications”) and Baltic countries (AB “Lietuvos telekomas” (Lithuania), “Lattelekom” (Lalvia) and “Eesti Telefon” (Estonia)) showed that in 2001 a debt ratio of German, British and French companies (0.48, 0.55 and 0.77 accordingly) was higher than the debt ratio of other companies.Net profit ratio of AB “Lietuvos telekomas” and “Lattelekom” was the highest in 2001 (17%), while “Deutsche Telekom” and “France Telecom” suffered losses (-7% and -19% accordingly). In 2001 “France Telecom” and AB “Lietuvos telekomas” had the lowest expenses ratio (0.41 and 0.47 accordingly), and “Telia” expenses ratio was the worst (0.71). “Deutsche Telekom” and “France Telecom” bad the biggest probability of bankruptcy in 2001 (1.35 and 1.48 accordingly).Telecommunications companies such as “Deutsche Telekom”, “France Telecom” and “British Telecom” that invested in 3G licences in 2000-2001 suffered huge losses. The main reasons for that were:A) Due to tough competition between the companies in European Union countries, telecommunications companies were forced to lower a profit margin;B) Forecast of telecommunications companies on capacity sales sharp increase was too optimistic and the investments to network infrastructure did not pay back;C) Purchase of 3G licences negatively influenced financial results of the companies.In addition, AB “Lietuvos telekomas” activities were analysed in order to forecast Lithuanian company opportunities in the liberalized telecommunications market, which will happen in 2003. The analysis showed that Lithuanian telecommunications market is growing rapidly as demand for telecommunications services is increasing. AB “Lietuvos telekomas” was financially strong, competitive, had a modem telecommunications network. new customer accounting and billing system, and was well prepared for the market liberalization.